IMPACT OF HATHA YOGA PRACTICES AND MANTRA CHANTING ON SELECTED PHYSIOLOGICAL VARIABLE AMONG AUTISTIC CHILDREN - K.K. Suresh; V. Duraisami (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the present study was to find out the Impact of Hatha Yoga Practices and Mantra Chanting on Selected Physiological Variable Among Autistic Children. The study was conducted on 45 Autistic Children. Totally three groups, namely, control & experimental group I & II, consisting of 15 Autistic Children underwent six weeks of practice in Hatha Yoga Practices and Mantra Chanting whereas the control group did not under go any type of training. The Heart Rate was measured before and after the experimentation using the Citizen Equipment to measure the Heart Rate. The data were analyzed by Analysis of Co-variance (ANCOVA) and it was concluded that the Hatha Yoga Practices and Mantra Chanting had significant (P < 0.05) effect on the Heart Rate level.